History of drug pricing reform in the United States: From policy foundations to latest reforms - Sujith Ramachandran; Arman Arabshomali; John Coster (Health Affairs Scholar, 2026)
Abstract This article examines the historical evolution of prescription drug pricing policy in the United States from the 1960s through 2025, highlighting how incremental reforms have produced a complex and fragmented system. It traces the foundations of drug pricing across Medicaid, Medicare, the Veterans Affairs (VA) system, and the 340B Drug Discount program, emphasizing the development of key pricing benchmarks such as Average Wholesale Price (AWP), Average Manufacturer Price (AMP), and Average Sales Price (ASP). The analysis details major legislative milestones affecting drug pricing, including the Omnibus Budget Reconciliation Act (OBRA) of 1990, the Medicare Modernization Act (MMA) of 2003, the Affordable Care Act (ACA) on 2010, and the Inflation Reduction Act (IRA) of 2022, and explains how these reforms reshaped reimbursement, rebates, cost of the prescription drugs, and access to medications. The article also identifies the various consequences of policy design, including the Medicaid “best price” provisions, growth in state Medicaid program supplemental rebates, and changes in prescription drug spending and reimbursement. Understanding the trajectory of policy reform is critical to identifying opportunities for improving affordability, access, and transparency in prescription drug markets.